A Web Application For Playfair Cipher Cryptography: Method and Implementation - Argia Putri Ramadhani; Apriliana Vera Ardiyanti; Erni Widarti (Journal of Software Engineering and Multimedia (JASMED), 2025)
Amidst the increasing digital threats, understanding the basic principles of cryptography is crucial for data security education. While the Playfair Cipher remains a valuable classical algorithm, its manual use is prone to human error and is not compatible with modern computing systems. This research aims to address these issues by upgrading the Playfair Cipher through a software engineering approach, creating a web application that runs using HTML, CSS, and JavaScript. Unlike previous research that focused on descriptive analysis, this research emphasizes the application of new technologies by designing a structured client-side architecture, resulting in seamless processing and server-side execution. The application features a responsive user interface (UI) designed for easy user interaction and immediate visual feedback while constructing key matrices and solving bigrams. The results show that the application achieves 100% accuracy in validating manual logic, especially when verifying the ciphertext "CVSMOBLIMAPUOYHDBY," and offers highly efficient computational performance. This research provides a powerful and interactive software tool that upgrades classical methods and offers an extensible solution for algorithm validation and data security education.